Optimization of energy consumption in mobile Ad-Hoc networks with a swarm intelligence-based ABC algorithm - Vijay U. Rathod; Shyamrao V. Gumaste; Ramakrishna Guttula; Shrikant Zade; Ramanpreet Singh (Discover Applied Sciences)
Abstract Mobile Ad-hoc Networks (MANETs) consist of decentralized, self-organizing, and self-healing wireless nodes that form routes dynamically by selecting paths with the fewest viable intermediate nodes. Since transmission power consumption is closely tied to inter-node distance, energy levels play a critical role in route selection. This study introduces an enhancement to the Dynamic Source Routing (DSR) protocol using the Artificial Bee Colony (ABC) algorithm and swarm intelligence. The proposed BEE Inspired Dynamic Source Routing (BEEDSR) protocol enhances energy efficiency by utilizing the ABC algorithm to determine the most energy-efficient path between source and destination nodes. Results and performance assessment of BEEDSR against the standard DSR and the BEE Inspired Protocol (BEEIP) reveals superior results: a throughput increase of 11.47% and 27.76%, reduced energy consumption by 0.74% and 2.25%, decreased end-to-end (E2E) delay by 37.81% and 48.33%, lower routing overhead by 30.88% and 47.25%, and improved Packet Delivery Ratio (PDR) by 0.092% and 0.180%, respectively. The results indicate that BEEDSR significantly improves routing efficiency, reduces energy consumption, and delivers superior performance in managing node mobility and varying packet sizes compared to conventional DSR and BEEIP protocols.